Age and Body Mass Index (BMI) with the Incidence of Uterine Myoma - Rini Asty Wulandari; Dwi Faradina; Haflin Soraya Hutagalung; Afrida Aryani Nasution (Sarana Ilmu Indonesia (Salnesia), 2026)
Uterine fibroids were benign tumors that typically affected women of reproductive age. They developed from the smooth muscle of the uterus. Uterine fibroids are thought to grow in response to a combination of variables, one of which is age and the other is body mass index (BMI). Patients treated at the Gynecology Clinic of Prof. Dr. Chairuddin Panusunan Lubis Teaching Hospital in Medan were surveyed to determine the relationship between age, body mass index (BMI), and uterine fibroids. This study used an observational analytical design with a hospital-based case-control approach. Of the 281 patients enrolled between July 2022 and July 2024, 160 met the inclusion criteria and were analyzed, consisting of 80 patients with uterine fibroids and 80 patients without uterine fibroids. Data were obtained from medical records and structured interviews, then analyzed using the Chi-square test through SPSS software version 27. The results of the study showed that the majority of uterine myoma patients were in the 35–50 years age group (73.8%) and had an obese BMI (68.8%). Bivariate analysis showed a significant relationship between age and body mass index (BMI) with the incidence of uterine myoma (p < 0,001). This study concludes that age and body mass index (BMI) are significantly associated with the incidence of uterine myoma. The highest risk is found among women of mature reproductive age (35–50 years) and those with an obese BMI category.